Pengaruh Disiplin, Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. XYZ - Ahmed Asad Purbaya; Alkusani Alkusani; Heru Baskoro (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
The increasingly advanced development of the times has made competition in the business world very rapid. This requires companies to be able to increase their competitiveness in maintaining the company's survival. The capabilities of human resources must be provided with good facilities to be able to produce quality output. Quantitative research methods were used in this research. Researchers collected data from respondents using questionnaires. The population of this research is employees of PT. XYZ, the number of samples in this study was 64 people. The results of this research show that work discipline has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, work environment has a positive and significant effect on employee performance, Work Discipline Variables, Work Motivation Variables and Work Environment Variables have a simultaneous effect on employee performance